Publication Trends in Manuscript Research (2011–2020): A Bibliometric Analysis - Rajan , Sarita S.; Esmail , S. Mohamed (Research Highlights in Language, Literature and Education Vol. 3, 2023)
The purpose of the current study is to characterise and provide a summary of research publications lined with manuscript libraries. Over the course of human history, writing and printing have advanced significantly, and the manuscript culture has followed. We must maintain contact with the individuals who created each of our individual accessions in order to preserve archives. It protects the literary, linguistic, artistic, and cultural heritage while maintaining the pulse of the past. The study result shows United States of America exceed in the area of research in manuscript libraries. The use of new trends and cutting-edge technologies to adapt to the expanded landscapes of the digital humanities and scholarly communications has produced a number of results, including top collaborators at the journal and institute levels, language, country, and keyword distribution. How to approach the publications in conjunction with manuscript libraries around the world is a challenge.